Assistance in Implementing Digital Population Identity Services in Kraton Village to Enhance Digital-Based Population Administration Services - Millatus Sholihah; Titis Srimurni; Ning Mukti Indrayani; Dini Maisaro; Julia Fatmawati (Trescode Green Organization, 2025)
Advancements in information technology and the evolution of society toward the Society 5.0 era require governments and public organizations to integrate digital technology into public service delivery. One form of e-government implementation in the field of population administration is the application of the Digital Population Identity (IKD). This community service initiative was conducted through assistance in Digital Population Identity services in Kraton Village, Lumajang Regency. This activity serves as an initiative to support the success of IKD registration and activation through a direct approach to citizens requiring population administration services. The assistance-based approach was selected to support the village government in identifying potential users and socialising IKD more effectively. As pioneers of digital transformation in Indonesia, Millennials and Generation Z play a strategic role in driving technology adoption within society. Consequently, this assistance activity involves university students as implementing partners to support government efforts in enhancing the quality of digital-based population administration services. The expected outcomes of this initiative include increased understanding among village government officials regarding IKD socialization, a higher number of citizens activating their Digital Population Identity, and enhanced public awareness regarding the importance of utilizing technology to access population administration services in quick, and efficient way.